Association of Candidate Gene Polymorphisms with Tick Resistance in Kankrej and Holstein-Friesian Crossbred Cattle - K Chaudhary, Ashok; Prakash Gupta, Jay; D Chaudhari, Jagdish; B Chaudhari, Arth; Kunhipurayil, Shyma; B Purohit, Pravin (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study investigated polymorphisms in four candidate genes (CD14, SPP1, CD209, and EFR3A) previously reported to be associated  with tick resistance or immune mechanisms against tick and tick-borne diseases (TTBDs). PCR-RFLP was used to genotype Kankrej and  Holstein Friesian crossbred (HFCB) cattle, and associations between gene variants and tick infestation status were evaluated. CD14 and  CD209 genes showed polymorphisms in crossbreds, while Kankrej cattle were monomorphic for these loci. The SPP1 and EFR3A genes  were monomorphic in both breeds. Although CD14 polymorphisms were not significantly associated with tick resistance, animals with  the BB genotype had reduced odds of infestation compared to AB. A significant association was observed for CD209, where the AA  genotype conferred a 12.89 fold higher susceptibility to ticks than AB. These findings highlight the potential of CD209 as a genetic marker  for breeding programs aimed at enhancing tick resistance, while also emphasizing the breed-specific distribution of polymorphisms  in candidate immune genes.
Keywords: Candidate gene; Kankrej; PCR-RFLP; Tick resistance